What is the product of (3x + 6)(3x - 6)?

(3x + 6)(3x - 6) = 9x^2 - 18x + 18x - 36 = 9x^2 - 36

Question

Asked 2/20/2013 12:24:06 PM

Updated 7/1/2016 12:00:35 PM

1 Answer/Comment

Edited by Andrew. [7/1/2016 12:00:04 PM]

Rating

3

(3x + 6)(3x - 6)

= 9x^2 - 18x + 18x - 36

= 9x^2 - 36

= 9x^2 - 18x + 18x - 36

= 9x^2 - 36

Added 7/1/2016 12:00:35 PM

This answer has been confirmed as correct and helpful.

What is the difference of (4x^2-7x^3)-(8x^2-9x^3)? **Weegy:** (4x^2 - 7x^3) - (8x^2 - 9x^3)= 2x^3 - 4x^2 (More)

Question

Expert Answered

Updated 7/1/2016 12:01:53 PM

0 Answers/Comments

What is the product of (7x - 2)(5x + 3)? **Weegy:**
(7x - 2)(5x + 3)
= 35x^2 + 21x - 10x - 6
= 35x^2 + 11x - 6
(More)

Question

Expert Answered

Updated 7/1/2016 12:02:59 PM

0 Answers/Comments

Simplify the expression 8(4x + 2)? **Weegy:** 8(4x + 2) = 32x + 16 (More)

Question

Expert Answered

Updated 7/1/2016 12:04:41 PM

0 Answers/Comments

30,208,896

questions answered

There are no comments.